2016
DOI: 10.1016/j.bone.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and trabecular deterioration in mouse models of Roux-en-Y gastric bypass

Abstract: Roux-en-Y gastric bypass (RYGB) is a profoundly effective treatment for severe obesity, but results in significant bone loss in patients. Developing a murine model that recapitulates this skeletal phenotype will provide a robust tool with which to study the physiologic mechanisms of this bone loss. We studied adult male C57BL/6J mice who underwent either RYGB or sham operation. Twelve weeks after surgery, we characterized biochemical bone markers (parathyroid hormone, PTH; C-telopeptide, CTX; and type 1 procol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…The same conclusion can be drawn from the differences seen in trabecular bone in male mice. Although some of our findings showed lower trabecular number and higher trabecular separation in animals allocated to the SOY group, a finding that is seen in animal models that simulate bone loss patterns [26], the lack of differences across groups based on mechanical testing further suggest that these changes may have been observed at random.…”
Section: Discussionmentioning
confidence: 74%
“…The same conclusion can be drawn from the differences seen in trabecular bone in male mice. Although some of our findings showed lower trabecular number and higher trabecular separation in animals allocated to the SOY group, a finding that is seen in animal models that simulate bone loss patterns [26], the lack of differences across groups based on mechanical testing further suggest that these changes may have been observed at random.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study from our group demonstrated that obese, T2DM mice showed decreased serum levels of bone turnover biomarkers C-terminal telopeptide of type I collagen (CTX) and osteocalcin (OCN) 32 . Meanwhile, several studies agree that the expression levels of CTX, OCN and/or P1NP in bone are affected after gastric bypass 33 , 34 . The suggested alteration of the bone remodeling of both mice groups goes in line with the dramatic decrease of trabecular BV/TV found in this study, given the fact that the trabecular compartment is an area more metabolically active than the cortex, and prone to high levels of remodeling 35 .…”
Section: Discussionmentioning
confidence: 98%
“…Changes in weight and body composition measures were more widely correlated with bone loss after SG than RYGB, which may suggest that mechanical unloading may play a more important role in the pathophysiology of bone loss after SG. Indeed, animal studies suggest that the mechanism of bone loss after RYGB is independent of weight loss (37, 38). RYGB, which bypasses the duodenum and proximal jejunum, is associated with impaired absorption of calcium and vitamin D, key determinants of bone health (34, 39).…”
Section: Discussionmentioning
confidence: 99%